3D sodium (Na-23) magnetic resonance fingerprinting for time-efficient relaxometric mapping - Kratzer, Fabian J.; Flassbeck, Sebastian; Schmitter, Sebastian; Wilferth, Tobias; Magill, Arthur W.; Knowles, Benjamin R.; Platt, Tanja; Bachert, Peter; Ladd, Mark E.; Nagel, Armin Michael (Magnetic Resonance in Medicine, 2021)
Purpose: To develop a framework for 3D sodium (Na-23) MR fingerprinting (MRF), based on irreducible spherical tensor operators with tailored flip angle (FA) pattern and time-efficient data acquisition for simultaneous quantification of T-1, T-2l*, T-2s*, and T-2* in addition to Delta B-0.
CRIS-Team WoS Importer:2021-06-11